Perancangan Aplikasi Panduan Merawat Lansia dengan Memperhatikan Asupan Makanan Berbasis Web - Febriani, Wahyu Eka, Hernawan Sulistyantanto, S.T., M.T (2016)
Elderly care or treatment is a very interesting thing for a nutritionist even for families in general. Elderly group that is rarely considered their food intake needs attention because, although the elderly, the elderly are also entitled to proper food intake.Application Guide Caring for the Elderly is a system created in order to monitor and show the food intake which is appropriate for the elderly, as well as to ease the operation.This application is web based. The method used is a qualitative method. This method is an analysis, which analyzes the data and facts and expose it in a description to get a conclusion, this method is also oriented to process its application in the form of data input and the elderly get the results in the form of data tables proper food intake for the elderly.Calculation of the calories for the elderly is also needed because the elderly are vulnerable to disease, thus each needs his daily calories should be noted. Application Guide caring for Elderly Healthy has been through a testing phase with the use of a detailed questionnaire, and the results of testing applications it can be concluded that the application had been successful with the percentage of success